2019
DOI: 10.1002/cncr.31861
|View full text |Cite|
|
Sign up to set email alerts
|

The role of autologous stem cell transplantation in patients with nodal peripheral T‐cell lymphomas in first complete remission: Report from COMPLETE, a prospective, multicenter cohort study

Abstract: Background The role of autologous stem cell transplantation (ASCT) in the first complete remission (CR1) of peripheral T‐cell lymphomas (PTCLs) is not well defined. This study analyzed the impact of ASCT on the clinical outcomes of patients with newly diagnosed PTCL in CR1. Methods Patients with newly diagnosed, histologically confirmed, aggressive PTCL were prospectively enrolled into the Comprehensive Oncology Measures for Peripheral T‐Cell Lymphoma Treatment (COMPLETE) study, and those in CR1 were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
89
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 26 publications
9
89
1
1
Order By: Relevance
“…In addition, while NCCN guidelines suggest that HDT be considered for consolidation in first remission for most aggressive T cell lymphomas except for ALK+ anaplastic large cell lymphomas, only a proportion of patients undergo HDT after initial therapy. In a report from the COMPLETE registry, a prospective outcomes registry of patients with aggressive T cell lymphomas in the United States, Park et al report that of 119 patients with nodal T cell lymphomas who achieved a CR to front line therapy, only 36 (30%) underwent consolidation ASCT . The use of autologous or allogeneic stem cell transplantation in HSTCLs and PGDTCLs has not been well defined in large clinical trials as it has been in the EATLs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while NCCN guidelines suggest that HDT be considered for consolidation in first remission for most aggressive T cell lymphomas except for ALK+ anaplastic large cell lymphomas, only a proportion of patients undergo HDT after initial therapy. In a report from the COMPLETE registry, a prospective outcomes registry of patients with aggressive T cell lymphomas in the United States, Park et al report that of 119 patients with nodal T cell lymphomas who achieved a CR to front line therapy, only 36 (30%) underwent consolidation ASCT . The use of autologous or allogeneic stem cell transplantation in HSTCLs and PGDTCLs has not been well defined in large clinical trials as it has been in the EATLs.…”
Section: Discussionmentioning
confidence: 99%
“…At a median follow‐up of 2.8 years, the median survival of the transplanted group has not yet been reached, while it is 57.6 months for those without transplant. ASCT was associated a with a hazard ratio of 0.37 and was an independent risk factor for survival . The NCCN guidelines for NHL recommend consideration of ASCT for patients with aggressive PTCL who achieve a CR or PR after primary therapy and are eligible based on age and co‐morbidity .…”
Section: Principles Of Managing Ptcl In 2019mentioning
confidence: 99%
“…The data suggested that, for younger patients with MTCL, ASCT remains the preferred consolidation, in particular because patients who relapse after ASCT have some probability of being successfully salvaged with alloSCT. Table 1 [71][72][73][75][76][77][78][79][80][81] shares the published results of ASCT trials in MTCL both in first CR (CR1) and beyond CR1. In conclusion, it appears that ASCT has a role for patients with MTCL in CR1; patients with ALKpositive ALCL also have a favorable outcome with conventional chemotherapy, allowing for the possibility of delaying this strategy until it can be delivered in a salvage setting.…”
Section: The Role Of Autologous Sctmentioning
confidence: 63%
“…More recently, the COMPLETE registry (Comprehensive Oncology Measures for Peripheral T-Cell Lymphoma Treatment) reported on a large, multi-institutional, prospective cohort directly comparing the survival outcomes of patients who had nodal MTCL with or without consolidative ASCT in first remission. 73 All histologies of MTCL were included, with the exclusion of large granular lymphocyte leukemias of T-cell origin, precursor T/NK neoplasms, mycosis fungoides, Sezary syndrome, and primary cutaneous CD30-positive disorders. A total of 213 patients were identified as having achieved CR after frontline therapy, 119 of whom had a nodal MTCL, including PTCL-NOS, ALK-negative ALCL, and AITL.…”
Section: The Role Of Autologous Sctmentioning
confidence: 99%